Assessment of knowledge and perception toward magnetic resonance imaging (MRI) safety among healthcare workers / Nur Nadiah Syafawani Abd Aziz, Wan Farah Wahida Che Zakaria and Lyana Shahirah Mohamad Yamin - Abd Aziz, Nur Nadiah Syafawani; Che Zakaria, Wan Farah Wahida; Mohamad Yamin, Lyana Shahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
The knowledge of healthcare workers about magnetic resonance imaging (MRI) safety is necessary to assure the safety and comfort of patients as well as ensure a smooth workflow. The aim of this study was to assess the knowledge and perception of Magnetic Resonance Imaging (MRI) safety among healthcare workers. A cross-sectional online survey of 132 healthcare workers was conducted between June and August 2022. The survey instrument consisted of demographic characteristics, the basic knowledge of the MRI and the perception of healthcare workers toward MRI safety. Most of the participants were female, aged group of 20 to 29 years old with diploma certificates. Based on the results, most of the healthcare workers have good knowledge with a 24.2% score, 36.4% with moderate knowledge and 39.4% are considered low knowledge regarding MRI safety. In terms of perception of MRI safety, 17.4% of healthcare workers have a high perception, while 47% have a moderate one and 35.6% have a low one. The results show that there is no association between demographic variables with the level of knowledge and perception of MRI safety.